Experimental study and numerical modeling of micro-channel cooler with micro-pipes for high-power diode laser arrays. (5th December 2015) - Kozłowska, Anna; Łapka, Piotr; Seredyński, Mirosław; Teodorczyk, Marian; Dąbrowska-Tumańska, Elżbieta
Abstract: A miniaturized micro-channel cooler with micro-pipes that transport cooling liquid was numerically modeled and experimentally studied. A prototype copper cooler with glass micro-pipes was manufactured and tested. An experimental arrangement for investigations of cooling performance of the proposed device was built. An infrared imaging method was employed for temperature profiling of high-power laser bar mounted on the cooler. Concurrently, mathematical and fully three-dimensional numerical models of the proposed new design of a cooler were developed and a series of thermo-fluid numerical simulations were performed for various mass flow rates of the cooling medium and different powers of laser diode. Obtained results were compared with experimental measurements and showed generally a good agreement. The possible origin of some discrepancies at boundaries was discussed. Both experimental and numerical findings indicate that the proposed cooler construction is an interesting solution for high-power laser diode arrays. Highlights: Miniaturized construction of micro-channel cooler with micro-pipes was numerically modeled and verified experimentally. Prototype copper micro-channel cooler comprising of glass micro-pipes was built and tested. Infrared imaging was employed for temperature profiling of laser array mounted on the cooler. A novel fully 3D numerical model of micro-heat sink was developed. An agreement of numerical and experimental results was obtained (relative L2 norm error < 5%).